Transplante alogênico de paratireoide de doador vivo como tratamento do hipoparatireoidismo pós-cirúrgico persistente - Gadelha, Daniel Duarte (2023)
Hypoparathyroidism is a disorder characterized by deficient or inappropriately low parathyroid hormone (PTH) secretion, leading to hypocalcemia and hyperphosphatemia. The standard clinical treatment has been used for decades, which consists of calcium and vitamin (calcitriol) replacement. However, this treatment shows inefficacy, leading to maintenance or worsening of the conditions already related to hypoparathyroidism (fatigue, muscle cramps, paresthesia, seizures, intracerebral calcifications, cognitive dysfunction, and renal stones/nephrocalcinosis). Therapies based on recombinant human parathyroid hormone (rhPTH) have emerged in recent years but still have low availability mainly due to their high cost. Despite few reports in the literature, parathyroid allotransplantation has been described as an alternative strategy to treat more severe cases. Thus, this study aimed at implementing a viable parathyroid allotransplantation protocol, still unpublished in Brazil and applicable to patients who have severe hypoparathyroidism, refractory to conventional treatment. The patients recruited as donors had end-stage chronic kidney disease and hyperparathyroidism awaiting for surgery. Parathyroid tissue was removed, prepared and immediately implanted in the non-dominant forearm of the recipient. Donors and recipients were ABO-compatible, and immunological screening was performed in two cases (HLA typing, Panel Reactive Antibody, and crossmatch tests). A short-term immunosuppressive regimen was adopted, which consists of three days of methylprednisolone followed by seven days of prednisone. The first allograft showed no evidence of functionality 12 months after transplant. In the following two patients, serum PTH levels did not increased as expected. However, serum calcium levels increased, and both patients experienced relief from hypocalcemic symptoms. In Case 2, oral supplementation decreased to half of the initial dose one month after transplantation and to one-fifth at the end of a 12-month follow-up period. In Case 3, intravenous calcium could be discontinued one week post-transplantation, and it was not yet required. PTH levels increased in Case 4 and hypocalcemic symptoms also reduced. No serious adverse events were observed. In conclusion, parathyroid allotransplantation showed to be safe and effective, and it can be considered for severe hypoparathyroidism. This is an innovative and not yet described procedure in Brazil. The procedure demonstrates to be an excellent option of treatment for refractory cases and it has the advantage of being low cost. Further studies with longer follow-up and greater number of patients are needed to confirm such efficacy in the long term.